CLINICAL MANIFESTATIONS OF DNMT1 MUTATIONS. Issue 11 (14th October 2015) - Fox, Robin; Gosal, David; Ealing, John; Murphy, Helen
Abstract : DNMT1 gene mutations have been previously associated with neurological syndromes in small numbers of patients. We present seven cases – a patient with a previously unreported DNMT1 mutation and a family with six members affected by a more classical DNMT1 syndrome. A 20-year-old patient with a history of common variable immune deficiency presented with sensory loss. He developed a syndrome of hereditary sensory and autonomic neuropathy (HSAN1E), cataplexy, cerebellar atrophy, deafness, and cutaneous manifestations of a scleroderma spectrum disorder. There was no family history. Genetic testing revealed the patient was heterozygous for a previously unreported in-frame deletion mutation, c.1635_1637delCAA p.(Asn545del) in the DNMT1 gene exon 20. Parental DNA analysis suggested a de novo occurrence. A 53-year-old female patient presented with unsteadiness and falls. On assessment she was found to have cerebellar ataxia, bilateral ptosis, deafness and narcolepsy. Questioning revealed five further affected members of her family with the same clinical syndrome, in an autosomal dominant inheritance pattern. Genetic testing revealed a missense mutation in the exon 21 region of the DNMT1 gene – p.Ala570Val. DNMT1 mutations, whilst rare, are associated with a specific constellation of neurological features and increased recognition will lead to an increased understanding of this condition.